Role of radiotherapy and chemotherapy in the risk of leukemia after childhood cancer: An international pooled analysis. Issue 9 (9th November 2020) - Allodji, Rodrigue S.; Tucker, Margaret A.; Hawkins, Michael M.; Le Deley, Marie‐Cécile; Veres, Cristina; Weathers, Rita; Howell, Rebecca; Winter, Dave; Haddy, Nadia; Rubino, Carole; Diallo, Ibrahima; Little, Mark P.; et al.
Abstract: Childhood cancer survivors are at increased risk for second primary leukemia (SPL), but there is little consensus on the magnitude of some risk factors because of the small size of previous studies. We performed a pooled analysis of all published studies with detailed treatment data, including estimated active bone marrow (ABM) dose received during radiation therapy and doses of specific chemotherapeutic agents for childhood cancer diagnosed from 1930 through 2000, in order to more thoroughly investigate treatment‐related risks of SPL. A total of 147 SPL cases (of which 69% were acute myeloid leukemia [AML]) were individually matched to 522 controls, all from four case‐control studies including patients from six countries (France, United Kingdom, United States, Canada, Italy and Netherlands). Odds ratios (OR) and corresponding 95% confidence intervals (CIs) were calculated using conditional logistic regression, and the excess OR per Gray (EOR/Gy) was also calculated. After accounting for the other therapies received, topoisomerase II inhibitor was associated with an increased SPL risk (highest tertile vs none: OR = 10.0, 95% CI: 3.7‐27.3). Radiation dose to the ABM was also associated with increased SPL risk among those not receiving chemotherapy (EOR/Gy = 1.6, 95% CI: 0.1‐14.3), but not among those who received chemotherapy (CT). SPL were most likely to occur in the first decade following cancer treatment. Results were similar when analyses were restricted to AML. The evidence of interaction between radiation and CT has implications for leukemogenic mechanism. The results for topoisomerase II inhibitors are particularly important given their increasing use to treat childhood cancer. Abstract : What's new? Childhood cancer survivors are at increased risk for second primary leukemia (SPL), but which treatments confer the greatest risk? In this study, the authors found that topoisomerase II inhibitors increased the risk of SPL by as much as 10‐fold, which was far higher than for other chemotherapies. Radiation therapy also increased the subsequent risk of SPL, but only in patients who didn't also receive chemotherapy. Given the poor prognosis of SPL, these results should help inform surveillance guidelines for childhood cancer survivors, and guide assessment of leukemia risks for specific treatment protocols.